Gemeinschaft versus Gesellschaft: Cooperatives and the problem of free-riding in the provision of collective goods - Pietrzak, Michał; Chlebicka, Aleksandra (Social Entrepreneurship Review, 2023)
Background: Cooperatives are unique entities that combine both non-profit and business attributes, reflecting the dual nature of Gemeinschaft and Gesellschaft. Research objectives: This article aims to explore the hybrid nature of cooperatives and the tension between community and business aspects in the context of the provision of collective goods. Specifically, we focused on the free-riding problem, which can harm the viability of cooperatives. Research design and methods: We based the article on critical analysis and discussion of the literature. The research questions were as follows: What is the inherent nature of cooperatives? What is the essence of the free-rider problem in cooperatives? How could the dual nature of cooperatives help deal with the problem of free-riding? Results: We discussed different Gemeinschaft-based approaches to mitigate free riding, such as kinship selection, direct reciprocity, and indirect reciprocity, which, however, create limitations on the size of the group of cooperators. There is tension between Gemeinschaft and Gesellschaft, as increasing membership for economic growth can lead to the erosion of social capital. We discussed three possible solutions, including massification, privatization, and leveraging the possibilities of online communities. Conclusions: Only the last approach, namely leveraging possibilities of online communities offers the solution to the difficult situation caused by the tension between Gemeinschaft and Gesellschaft as it does not violate the cooperative identity while still allowing for increased scale of the operations.